Sheltered from the heat? How tents and shade covers may unintentionally increase air temperature exposures to unsheltered communities - Joseph Karanja; Jaime Vieira; Jennifer Vanos (Elsevier, 2023)
Objective: Heat vulnerability and homelessness are central public health concerns in cities globally, and public health implementation should address these two challenges in tandem to minimize preventable heat-related morbidity and mortality. Populations facing unsheltered homelessness use tents (or similar shelters) with shading features to minimize sun and heat exposure. This study evaluates the efficacy of different tent cover (shading) materials and how they moderate the in-tent air temperature (Tair) exposures of tent users during extreme summer conditions. Study design: Within-tent Tair monitoring using Kestrel Drop devices occurred across three full typical summer days in Phoenix, Arizona in July 2022. Methods: In-tent Tair were statistically compared between six small side-by-side identical tents with different cover materials (control (no cover), mylar, white bedsheet, tarp, sunbrella fabric, aluminum foil), as well as with ambient Tair. Results: Using any tent resulted in higher daytime in-tent Tair than ambient Tair. Further, compared to a control tent, the Tair within tents shaded with sunbrella, tarp, and white bedsheet had significantly higher Tair at all times (2.36 °C, 2.46 °C, and 1.11 °C higher Tair, respectively), controlling for Tair and day/night. Conclusion: Adding cover materials over tents may increase heat risk to an already vulnerable population at certain times of the day. Higher in-tent Tair is attributable to the reduced ability for heat and vapor to escape, largely due to reduced ventilation (mixing). Local authorities and welfare associations should reconsider using unventilated tents for shading and promote more widespread, ventilated tents and shade to ensure that prevention efforts do not further marginalize the most vulnerable. Future work should incorporate more comprehensive measurements of solar radiation to quantify overall heat stress for exposure reduction techniques.